Digitalisasi Branding UMKM Gula Aren Cek Midut Di Batang Hari Ogan Tegineneng, Pesawaran, Lampung - Dian Refyawati; Salma Nur Aziza; Dwi Indah Murdiyanti; Rahman Pansamara; Chintiya Rahmi Maharani (CV. Multi Kreasi Media, 2023)
UMKM (Micro, Small & Medium Enterprises) are one of the means to improve the economy in Indonesia, but in the digital era like today UMKM need new innovations in terms of product marketing, namely by means of online marketing. To carry out online marketing, digital branding is needed. The 2023 Raden Intan Lampung UIN KKN service team based on economic independence partnered with one of the UMKM in Batang Hari Ogan Village, namely Gula Aren Cek Midut to carry out a branding digitization program. The purpose of digitizing branding for UMKM is to introduce UMKM in the digital world and is expected to expand the marketing reach of UMKM. The method used in this service is the appropriate technology method, which is a method used for activities that offer new science and technology that are more modern/new elements than the old science and technology. This digital branding program is carried out in several ways, namely (1) creating a logo (2) creating an Instagram account (3) registering for Google Maps (4) creating banners and (5) creating a link tree.